Identification of IQM-266, a Novel DREAM Ligand That Modulates KV4 Currents - Peraza, Diego A.; Cercós, Pilar; Miaja, Pablo; Merinero, Yaiza G.; Lagartera, Laura; Socuéllamos, Paula G.; Izquierdo García, Carolina; Sánchez, Sara A.; López-Hurtado, Alejandro; Martín-Martínez, Mercedes; Olivos-Oré, Luis A.; Naranjo, José R.; et al. (Frontiers in Molecular Neuroscience, 2019)
DREAM/KChIP3/calsenilin is a neuronal calcium sensor with multiple functions, including the regulation of A-type outward potassium currents (IA). This effect is mediated by the interaction between DREAM and KV4 potassium channels and it has been shown that small molecules that bind to DREAM modify channel function. A-type outward potassium current (IA) is responsible of the fast repolarization of neuron action potentials and frequency of firing. Using surface plasmon resonance assays and electrophysiological recordings of KV4.3/DREAM channels, we have identified IQM-266 as a DREAM ligand. IQM-266 inhibited the KV4.3/DREAM current in a concentration-, voltage-, and time-dependent-manner. By decreasing the peak current and slowing of the inactivation kinetics, IQM-266 led to an increase in the transmembrane charge (QKv4.3/DREAM) at a certain range of concentrations. The slowing of the recovery process and the increase of the inactivation from the closed-state inactivation degree are consistent with a preferential binding of IQM-266 to a pre-activated closed state of KV4.3/DREAM channels. Finally, in rat dorsal root ganglion neurons, IQM-266 inhibited the peak amplitude and slowed the inactivation of IA. Overall, the results presented here identify IQM-266 as a new chemical tool that might allow a better understanding of DREAM physiological role as well as modulation of neuronal IA in pathological processes.